Book Review: David Starkie (2008) Aviation Markets: Studies in Competition and Regulatory Reform - Guillaume Burghouwt (European Journal of Transport and Infrastructure Research, 2010)
Little more than 25 years ago, the airline industry was highly regulated. The industry is now placed within the market economy due to liberalization and privatization initiatives. Still, large parts of worldwide aviation remain subject to negligible competition. “Too often the instinct of the politician and administrator is to intervene, try to manage [..] the market and to generally distrust its working”. In his book, David Starkie provides a critical analysis of such policy initiatives by addressing the interplay of economic policy and aviation markets.